The Judge's Decision in Resolving the Marriage Problems of the Adhal Guardians (Case Study at the Religious Court of Serang Banten) - Ru’fah Abdullah (IHSA Institute, 2022)
The position of the guardian in marriage is mandatory, so that a marriage cannot be carried out, or the marriage is invalid due to the absence of a guardian, because the guardian is a pillar that must be fulfilled in the marriage contract, even though some scholars say that the guardian in a marriage contract is not a pillar that must be fulfilled. fulfilled, but it is only sunnah and a marriage that is carried out without the presence of a guardian in the marriage contract is not a legal defect, the marriage is still valid and does not become null and void. However, because Indonesia is specifically based on the Syafii madhab, and is supported by legislation in article 14 of the KHI, that among the pillars of marriage is the presence of a guardian. syara or not fulfilling the syara, even though the daughter still insists on marrying the man of her choice, in this case the judge can change the position of the guardian, due to the fact that the guardian. In deciding the case the judge is very careful, based on an agreement with the member judges, the judge must consider that between the applicant and the candidate there is no blood relationship, breastfeeding, it is not illegal to marry, both have persuaded the applicant's parents to marry off, the prospective applicant is already working, the applicant with the candidate kufu. There is a marriage refusal letter issued from the KUA, arguing that the guardian does not exist. The absolute power of judges is the authority of the Religious Courts in accordance with their absolutes, to settle cases of marriage, divorce, especially guardians of adhal. In principle, the Court is the end of solving problems in the family, especially in society so that when the problem is not resolved at home and in the extended family, the spearhead of the problem is brought to the Religious Courts, although the settlement must be through mediation.